2013
DOI: 10.2341/11-054-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er,Cr:YSGG Laser, Air Abrasion, and Silane Application on Repaired Shear Bond Strength of Composites

Abstract: Use of Er,Cr:YSGG (erbium, chromium: yttrium-scandium-gallium-garnet) laser does not improve the shear bond strength of the repaired resin; however, air abrasion with 50-lm aluminum oxide particles results in higher shear repair bond strength, and therefore is recommended prior to repair. Application of a silane coupling agent does not improve the shear bond strength of the repaired resin. SUMMARYAged resin composites have a limited number of carbon-carbon double bonds to adhere to a new layer of resin. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 23 publications
1
54
0
10
Order By: Relevance
“…An increase in the repair bond strength after the application of the diamond bur and cojet might be due to an increase in the surface roughness of the specimens and an increase in the bonded surface area, which was confirmed by SEM micrographs. Surface roughening has been reported to increase the surface energy and adhesive wettability [35,36]. Depending on these findings, grinding with a dimond bur, which is a quick and easy way of roughening, can be recommended as a pretreatment method for repair of CAD/CAM RNC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the repair bond strength after the application of the diamond bur and cojet might be due to an increase in the surface roughness of the specimens and an increase in the bonded surface area, which was confirmed by SEM micrographs. Surface roughening has been reported to increase the surface energy and adhesive wettability [35,36]. Depending on these findings, grinding with a dimond bur, which is a quick and easy way of roughening, can be recommended as a pretreatment method for repair of CAD/CAM RNC.…”
Section: Resultsmentioning
confidence: 99%
“…Surface treatment on the fractured surface of composite resin materials must be performed to obtain high bond strength between the materials. Although there is a great deal of information about the effect of several treatment methods on the bonding strength of composite restorations [18,20,27,[31][32][33][34][35][36][37][38][39][40][41][42], very limited data are available on the use of surface treatment of CAD/CAM resin-based materials [26,37,[43][44][45][46] to enhance their repair bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…Another study examined the reasons for this increased repair bond strength and the effects of laser irradiation on composite resins, and found that a change in the volume of the molten material produced strong expansion forces, which produced projections on the surface of the composite resin structure, and that droplets formed with the removal of molten material. 32 SEM showed that Er:YAG laser irradiation of a composite resin caused irregular pitting of the surface, which increased the surface area and resulted in a better stress distribution at the bonding area. 32 These studies concluded that when the output power decreased, greater adhesion was obtained.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, many studies have investigated different surface conditioning methods (acid etching, surface roughening, silane applications) to improve the bond strength of aged RBCs. [26][27][28] It would be interesting to investigate the impact of surface treatments of aged RBC restorations and its effect on its l-tbs with RLC's.…”
Section: Discussionmentioning
confidence: 99%